ÎN CĂUTAREA BLOCANTULUI NEUROMUSCULAR IDEAL: REVISTĂ A LITERATURII - Natalia BELÎI (Academy of Sciences of Moldova, 2022)
The modern general anesthesia is the one balanced, with orotracheal intubation, by combining drugs targeting different receptors. The selection of neuromuscular blocking agent for special circumstances in low-income countries is still a clinical dilemma. The present article reviews full format publications (n = 14) of last 5 years, following both known and new paralytic medication, both in terms of the 10 pharmacophysiological characteristics of ideal myorelaxant, as well as through the chain of patient's specific clinical conditions. Advances in this field of pharmacology are important, but it seems that they are still to be expected.